Navigierte urologische Chirurgie: Möglichkeiten und Grenzen aktueller Technik = Navigation in urological surgery : possibilities and limits of current techniques - Simpfendörfer, Tobias; Hatiboglu, Gencay; Hadaschik, Boris; Rassweiler, Jens; Hohenfellner, Markus; Teber, Dogu (Der Urologe, 2015)
Surgical navigation describes the concept of real-time processing and presentation of preoperative and intraoperative data from different sources to intraoperatively provide surgeons with additional cognitive support. Imaging methods such as 3D ultrasound, magnetic resonance imaging (MRI) and computed tomography (CT) and data from optical, electromagnetic or mechanical tracking methods are used. The resulting information of the navigation system will be presented by the means of visual methods. Mostly virtual reality or augmented reality visualization is used. There are different guidance systems for various disciplines introduced. Mostly it operates on rigid structures (bone, brain). For soft tissue navigation motion compensation and deformation detection are necessary. Therefore, marker-based tracking methods are used in several urological application examples; however, the systems are often still under development and have not yet arrived in the clinical routine.